2007
DOI: 10.1159/000110646
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Immune Responses in Tuberculosis Patients Are Related to Weight Loss That Coexists with an Immunoendocrine Imbalance

Abstract: The study’s objective was to examine whether factors related to the host status may bear some relation with the profile of the immune response displayed by tuberculosis (TB) patients. The in vitro immune response (antigen-driven lymphoproliferation and cytokine production) and the presence of alcoholism or disease-related factors, like heart and respiratory rates, and weight loss (body mass index, BMI) were investigated in 31 males with active, untreated TB. Compared to 16 age-matched healthy males, TB patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 59 publications
5
17
0
1
Order By: Relevance
“…According to the conclusions of a study that showed that weight loss was related to impaired immune responses in TB patients, 26 the finding in this study that being underweight (BMI 19) was associated with the intestinal parasitic infections only in PCs indicated that weight loss increased the risk of parasitic infection in persons with TB. The prevalence of anemia was 22-23% in this study and it was 35% in a study also conducted in rural area of central China, 27 which suggested that approximately 20-33% of the population in rural area of central China is at risk of malnutrition.…”
Section: Discussionsupporting
confidence: 50%
“…According to the conclusions of a study that showed that weight loss was related to impaired immune responses in TB patients, 26 the finding in this study that being underweight (BMI 19) was associated with the intestinal parasitic infections only in PCs indicated that weight loss increased the risk of parasitic infection in persons with TB. The prevalence of anemia was 22-23% in this study and it was 35% in a study also conducted in rural area of central China, 27 which suggested that approximately 20-33% of the population in rural area of central China is at risk of malnutrition.…”
Section: Discussionsupporting
confidence: 50%
“…It constitutes a major health problem worldwide and can lead to a consumption state, characterized by a remarkable weight loss [3,4] , traditionally defined as cachexia (Greek kakos = bad and hexis = condition). Because of its chronic nature, the disease is accompanied by excessive and/or protracted cytokine production liable to affect the immunoendocrine communication [3] .…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that the body mass index (BMI) is negatively associated with circulating IL-6 levels in patients with active TB. Stepwise regression analysis showed that 74% of the variability in IL-6 concentration was related to BMI, cortisol and IFN-␥ serum concentrations [4] . Adjusted analysis also showed that impaired in vitro immune responses of these TB patients (reduced lymphoproliferation and increased IL-10 and TGF-␤ production) lost statistically significance when adjusted to their BMI.…”
Section: Introductionmentioning
confidence: 99%
“…Stepwise regression analysis demonstrated that 74% of the variability in IL-6 concentrations was related to the BMI, and cortisol and IFN-␥ serum concentrations [96] . Collectively, these results indicate that the relation between weight loss and the abnormal immune response of TB patients is partly associated with the immunoendocrine imbalance observed in parallel.…”
Section: Clinical and Immunological Implications Of Systemic Immunoenmentioning
confidence: 99%